2019
DOI: 10.1093/ofid/ofz359.080
|View full text |Cite
|
Sign up to set email alerts
|

978. Changes in BMI Associated with Antiretroviral Regimens in Treatment-Experienced, Virologically Suppressed Individuals Living with HIV

Abstract: BackgroundA potential association between integrase inhibitor (INSTI) use and weight gain has been reported in people living with HIV (PLWH). We examined body mass index (BMI) increases after a switch to dolutegravir (DTG), elvitegravir/cobicistat (EVG/c), raltegravir (RAL), rilpivirine (RPV), or boosted darunavir (bDRV) among virologically suppressed ART-experienced PLWH.MethodsART-experienced, suppressed (ART-ES; baseline viral load < 200 copies/mL) PLWH ≥ 18 years of age initiating DTG, EVG/c, RAL, RPV, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…6 Integrase strand transfer inhibitor (INSTI)-containing ART regimens are the recommended first-line treatment of ARTnaive PLWH due to virologic efficacy and tolerability. 7 Despite excellent safety profiles and low side effect rates in Phase III clinical trials, data from randomized controlled trials and observational studies after widespread use of INSTIs in more diverse populations have shown increases in weight and BMI [8][9][10][11][12][13][14][15][16][17][18] particularly with dolutegravir [9][10][11]14,16,18 and among black and Hispanic women. 9,11 Recently, we showed that women switching to or adding an INSTI to their ART regimen in the pretenofovir alafenamide (TAF) era were more likely to experience clinically significant ( ‡7%) weight gain than women remaining on non-INSTI ART for an 18-month period: 22% versus 14%, with congruent findings across additional adiposity measures.…”
Section: Introductionmentioning
confidence: 99%
“…6 Integrase strand transfer inhibitor (INSTI)-containing ART regimens are the recommended first-line treatment of ARTnaive PLWH due to virologic efficacy and tolerability. 7 Despite excellent safety profiles and low side effect rates in Phase III clinical trials, data from randomized controlled trials and observational studies after widespread use of INSTIs in more diverse populations have shown increases in weight and BMI [8][9][10][11][12][13][14][15][16][17][18] particularly with dolutegravir [9][10][11]14,16,18 and among black and Hispanic women. 9,11 Recently, we showed that women switching to or adding an INSTI to their ART regimen in the pretenofovir alafenamide (TAF) era were more likely to experience clinically significant ( ‡7%) weight gain than women remaining on non-INSTI ART for an 18-month period: 22% versus 14%, with congruent findings across additional adiposity measures.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 While the INSTI class had demonstrated a proven tolerability profile, recent evidence suggests that among treatment-naïve patients or stable patients switching from previous ART, those initiated on an INSTI-based regimen were more likely to experience weight gain than those initiated on other types of ART regimens. [11][12][13][14] Recent DHHS guidelines also highlight that greater weight gain is observed among patients treated with INSTI-based regimens relative to PI-based regimens. 8 Furthermore, INSTI use has been associated with greater risk of metabolic outcomes, including diabetes mellitus.…”
mentioning
confidence: 99%